PRAKTEK AKUNTANSI DALAM DUNIA BISNIS - Nariman, Augustpaosa; Vennessa; Puteri, Annisa Fadila (Jurnal Serina Abdimas, 2024)
ABSTRACT The business needs professionals who have the ability to make financial reports and provide financial information to help management in making decisions. Accounting is the process of recording transactions and financial statement which include financial position and profit loss statements. The financial position consists of the company's assets and debts, while the profit and loss provides information on the amount of sales and operational costs incurred to generate company profits. Accounting knowledge can be taught at Senior High Schools (SMA) and Vocational High Schools (SMK) in the field of accounting which can be continued at university level, in Faculty of Economics, majoring in Accounting. Dewi Sartika Vocational School is a Vocational High School located in West Jakarta. The majors/competencies offered by the school are: Office Administration, Accounting, Marketing, and Computer and Network Engineering. The number of students majoring in Accounting is 28 people, consisting of 13 people in class 10, 9 people in class 11, 6 people in class 12 need knowledge to understanding the accounting cycle, accounting journals, financial statement, and the accounting profession. Permanent lecturers at the Faculty of Economics, Department of Accounting, Tarumanagara University provide accounting training includes the process of recording transactions and preparing financial reports as well as explaining the accounting profession. The training lasted smoothly one day at Dewi Sartika Vocational School, which was attended by 22 students and accounting teachers with the aim of providing students with a better understanding of the accounting process and the accounting profession ABSTRAK Dalam dunia bisnis sangat membutuhkan professional yang memiliki kemampuan dalam membuat laporan keuangan yang dapat memberikan informasi keuangan dalam membantu manajemen dalam pengambilan keputusan. Kemampuan tersebut tentu dipelajari dan diperoleh dari masa sekolah sampai ke perguruan tinggi. Akuntansi merupakan proses pencatatan transaksi dan penyusunan laporan keuangan perusahaan yang meliputi laporan posisi keuangan dan laporan laba rugi. Laporan posisi keuangan memberikan informasi mengenai aset dan hutang perusahaan, sedangkan laporan laba rugi memberikan informasi besarnya penjualan dan biaya-biaya operasional yang dikeluarkan untuk menghasilkan laba perusahaan. Ilmu akuntansi dapat diberikan pada Sekolah Menengah Atas (SMA) maupun Sekolah Menengah Kejuruan (SMK) di bidang akuntansi yang dapat dilanjutkan pada tingkat universitas khususnya Fakultas Ekonomi jurusan Akuntansi. SMK Dewi Sartika merupakan Sekolah Menengah Kejuruan yang terletak di Jakarta-Barat. Adapun jurusan/kompetensi yang ditawarkan oleh sekolah yaitu: Administrasi Perkantoran, Akuntansi, Pemasaran, dan Teknik Komputer dan jaringan. Jumlah siswa yang mengambil jurusan Akuntansi adalah sebanyak 28 orang yang terdiri dari kelas 10 sebanyak 13 orang, kelas 11 berjumlah 9 orang, kelas 12 berjumlah 6 orang. Siswa-siswi SMK yang mengambil jurusan Akuntansi sangat membutuhkan pengetahuan mengenai akuntansi yang meliputi pemahaman siklus akuntansi, jurnal transaksi, laporan keuangan, dan profesi Akuntansi yang bisa dijalankan. Dosen tetap Fakultas Ekonomi jurusan Akuntansi Universitas Tarumanagara memberikan pelatihan Akuntansi yang meliputi proses pencatatan transaksi keuangan dan penyusunan laporan keuangan serta penjelasan profesi akuntansi. Pelatihan berlangsung satu hari dengan lancar di SMK Dewi Sartika yang diikuti oleh 22 orang siswa dan guru akuntansi dengan tujuan agar Siswa-siswi dapat lebih memahami proses akuntansi dan profesi akuntansi.